Effect of an Eight-week Core Stability Training Program on the Functional Movement Screen Test Scores in Elite Goalball Players - Mahrokh Moghadam, Azadeh; Zarei, Mostafa; Mohammadi, Fariba (Physical treatments, 2021)
Purpose: This study aimed to investigate the effect of eight weeks of core stability training on the functional movement screen (FMS) test scores in elite goalball players. Methods: The study sample included 26 elite goalball players. The players were randomized into the two groups of experimental (n=13) and control (n=13). Besides, FMS was used to evaluate the study variables in both groups, before and after the eight weeks of training. After the pretest, the experimental group performed the core stability training using a Swiss ball, three days a week for eight weeks; the control group did the usual training. Then, the analysis of covariance at the significant level of 0.05 was used to analyze the obtained data. Results: The results showed a significant difference in the adjusted mean scores of the FMS test between the experimental and control groups (P=0.021). Conclusion: The positive effect of core stability training on the FMS test scores of the motor function in goalball players emphasizes the effectiveness of this training in core stability muscles. Therefore, it is suggested to use core stability training combined with exercises as an effective way to improve movement patterns and prevent injury in goalball players.